Strain localization analysis in materials containing randomly distributed voids: Competition between extension and shear failure modes. (September 2022) - Cadet, Clément; Besson, Jacques; Flouriot, Sylvain; Forest, Samuel; Kerfriden, Pierre; Lacourt, Laurent; de Rancourt, Victor
Abstract: Strain localization is often a precursor to the ductile failure of materials. This paper investigates plastic strain localization phenomena in the case of random microstructures, namely cubic cells made of an elastic-perfectly plastic matrix embedding distribution of identical non-overlapping spherical voids. The consideration of random microstructures allows for a better representation of the interaction between voids and greater diversity of failure modes than single-void (or unit) cells. The cells are simulated by means of the finite element (FE) method for proportional stress loading paths with controlled stress triaxiality and Lode parameters. Strain localization is detected by Rice's criterion computed at the cell level. This criterion is shown to accurately capture the onset of localization and the type of failure mode, either extension or shear banding. Moreover, the influence of the loading orientation, i.e. the orientation of the principal axes of the applied stress tensor with respect to the microstructure cube, is systematically studied. Significant anisotropy of failure behavior is observed, especially in the case of single void unit cells, which can be attributed to the intrinsic anisotropy of the simulation cells. Finally minimal failure strain values at localization with respect to all loading orientations are found. A zone of reduced ductility is observed under generalized shear loading conditions. Highlights: Ductile fracture is studied by simulating the failure of random microstructures. Rice's criterion allows to detect localization and shear/extension failure modes. A strong anisotropy of failure behavior is observed when rotating the loading. This intrinsic anisotropy is stronger in single void cells than in random cells. Minimal failure strain (T, L) response shows low ductility under generalized shear.